2019
DOI: 10.1590/1516-3180.2019.026906082019
|View full text |Cite
|
Sign up to set email alerts
|

Fetal structural anomalies diagnosed during the first, second and third trimesters of pregnancy using ultrasonography: a retrospective cohort study

Abstract: BACKGROUND: The prevalence of congenital abnormalities in general populations is approximately 3-5%. One of the most important applications of obstetric ultrasound is in detection of fetal structural defects. OBJECTIVE: To assess fetal structural anomalies diagnosed using ultrasound in the three trimesters of pregnancy. DESIGN AND SETTING: Retrospective cohort study at the Mário Palmério University Hospital of the University of Uberaba (Universidade de Uberaba, UNIUBE), from March 2014 to December 2016. METHOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 36 publications
2
24
1
1
Order By: Relevance
“…in Brazil and Sallout et al . in Saudi Arabia reported that genitourinary defects were the most frequently diagnosed anomalies during the prenatal period and at birth with detection rate of 76.7% 10,12 . In our present study, urogenital anomalies (including hydronephrosis, duplex kidney, multicystic dysplastic kidney and so on) and thoracic anomalies (including congenital diaphragmatic hernia and congenital pulmonary airway malformations) were the most frequently referred anomalies during the prenatal period comprising 31 and 30% of all antenatal consultations, respectively.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…in Brazil and Sallout et al . in Saudi Arabia reported that genitourinary defects were the most frequently diagnosed anomalies during the prenatal period and at birth with detection rate of 76.7% 10,12 . In our present study, urogenital anomalies (including hydronephrosis, duplex kidney, multicystic dysplastic kidney and so on) and thoracic anomalies (including congenital diaphragmatic hernia and congenital pulmonary airway malformations) were the most frequently referred anomalies during the prenatal period comprising 31 and 30% of all antenatal consultations, respectively.…”
Section: Discussionsupporting
confidence: 50%
“…The referral rate of surgical anomalies via our multidisciplinary perinatal surgical consultation scheme was 0.6%. This was lower than the expected prevalence of 1.9–3% as in other international literature; however, our study did not include records of stillbirth nor post‐mortem anomalies which would not be referred to our service via this scheme; therefore, it could not reflect the actual incidence in our population 1,2,10 . Some of the mild and less complex congenital anomalies such as mild antenatal hydronephrosis were not referred to this scheme for surgical counselling, which were counselled by obstetricians only after detection.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Owing to technological advances, the utility of first-trimester ultrasound between 11 and 14 weeks can be used beyond confirming viability, gestational age, chorionicity, amnionicity, and measuring the fetal nuchal translucency thickness to include fetal anatomic visualisation. 3 This case illustrated the importance of early anatomic surveillance and implies that during the first-trimester ultrasound, evaluation should include identification of two equal cerebral hemispheres, presence of choroid plexus, and appropriate posterior fossa size. Rossi et al support this assertion, describing that first-trimester ultrasound can identify approximately half (51%) of all significant fetal brain and spine anomalies.…”
Section: Discussionmentioning
confidence: 92%
“…8) de ned congenital malformation as "any morphological abnormality that dates to the embryonic or fetal period, regardless of the mechanism of its origin ". As radiological technology advances, fetal ultrasonography is an appropriate diagnostic standard for prenatal CNS anomalies and they can be visualized starting from the rst trimester, even as early as 6 weeks onwards (7,17,(27)(28)(29). The detection of CNS anomaly on ultrasound requires a systemic approach to direct into the nal diagnosis, evaluate the prognosis of the condition and outline the management plan accordingly.…”
Section: Resultsmentioning
confidence: 99%